Detection of prostate cancer with three-dimensional transrectal ultrasound: correlation with biopsy results - Zhao, H-X (The British Institute of Radiology., 2012)
OBJECTIVES: The aim of this study was to evaluate the role of three-dimensional transrectal ultrasound in the diagnosis of prostate cancer. METHODS: A total of 112 patients with elevated serum prostate-specific antigen (PSA) or a positive digital rectal examination were evaluated using three-dimensional greyscale transrectal ultrasound (3D-GS TRUS) and three-dimensional power Doppler sonography (3D-PDS). Target biopsies were obtained together with 12 core systematic biopsies. Pathological results were correlated with the imaging data. RESULTS: Cancers were detected in 269 biopsy sites from 41 patients. 229 sites of cancer were depicted by 3D-GS TRUS and 213 sites were depicted by 3D-PDS. 30 sites were missed by both 3D-GS TRUS and 3D-PDS. Abnormal prostate images depicted by 3D-GS TRUS and 3D-PDS were associated with lesions with a Gleason score of 6.9 or higher. CONCLUSION: The detection rates of prostate cancer were significantly improved with 3D-GS TRUS and 3D-PDS on serum PSA levels >10 ng ml(–1) or 20 ng ml(–1). 3D-GS TRUS and 3D-PDS may improve the biopsy yield by determining appropriate sites for target and systematic biopsies. The abnormalities detected by 3D ultrasound were associated with moderate- and high-grade prostate cancers. However, based on the number of false-negative TRUS results, the use of systematic prostate biopsies should not be eliminated.